Pengembangan Lembar Kerja Peserta Didik Berbasis Realistik Matematik Education (RME) pada Siswa Sekolah Dasar - Andita, Cahyo Dwi; Widaswari, Dea (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to produced Student Worksheet based on Realistic Mathematics Education (RME) which is valid, practical and effective on the topic of operations of integer calculation. The method in this study refers to the development of Realistic Matematic Education Based Mathematics Student Worksheets with the design and development of learning modules using a 4-D development model with four stages: definition (define), planning (design), development (development), and deployment (disseminate). According to the research findings, the Mathematics Student Worksheet Based on Realistic Mathematic Education, showed a percentage of 91,87% with a very practical category, so that it can be recommended for used in learning, especially material for operations of integer calculation . The test results showed a percentage of 85.70% with a very effective category. concluded that the student workshetts based realistic mathematic education (RME) was practically, valid and effective for use in learning process. Keywords: Realistik Matematik Education, Student Worksheet